2012
DOI: 10.1007/s00271-012-0368-7
|View full text |Cite
|
Sign up to set email alerts
|

Camelina water use and seed yield response to irrigation scheduling in an arid environment

Abstract: Camelina sativa (L.) Crantz is a promising, biodiesel-producing oilseed that could potentially be implemented as a low-input alternative crop for production in the arid southwestern USA. However, little is known about camelina's water use, irrigation management, and agronomic characteristics in this arid environment. Camelina experiments were conducted for 2 years (January to May in 2008 and 2010) in Maricopa, Arizona, to evaluate the effectiveness of previously developed heat unit and remote sensing basal cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
7
18
1
Order By: Relevance
“…Water use efficiencies observed here under a large number of overhead sprinkler irrigation levels had a wider range than those reported by Hunsaker et al (2013) with surface irrigation. Maximum WUE with overhead sprinkler (0.54-0.65 kg m -3 ) was higher than the 0.35 kg m -3 under surface irrigation.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Water use efficiencies observed here under a large number of overhead sprinkler irrigation levels had a wider range than those reported by Hunsaker et al (2013) with surface irrigation. Maximum WUE with overhead sprinkler (0.54-0.65 kg m -3 ) was higher than the 0.35 kg m -3 under surface irrigation.…”
Section: Discussioncontrasting
confidence: 47%
“…Scheduling of irrigations were linked to evapotranspiration (ET c ) estimates, calculated daily with FAO-56 dual crop coefficients (Allen et al, 1998;Mon et al, 2016). Seasonal basal crop coefficients (K cb ) used were from an empirically derived function based on camelina crop coefficient data obtained in prior field studies at this site (Hunsaker et al, 2013). A daily soil water balance estimated depletion of water in the camelina soil root zone, using irrigation and rainfall data.…”
Section: Methodsmentioning
confidence: 99%
“…The range of C. sativa seed oil content observed in this study was within the range reported in the previous literature [12,[23][24][25]27,29,32,35,37], but it was lower than the C. sativa seed oil content reported by McVay and Khan [31]. The lower C. sativa oil content reported in our study was most likely due to water deficit, which was consistent with the observations made by other studies [18,35,37,56]. The results from this study suggest that Columbia, Blaine Creek, Suneson and Ligena might perform well, under drier conditions; however, this study also points to the need for improving the oil content in available C. sativa cultivars.…”
Section: Oil Content Oil and Biodiesel Yieldsupporting
confidence: 91%
“…Although a legume, alfalfa removes large amounts of minerals from the soil, and might require significant fertilizer inputs for optimum yield [17]. In contrast, C. sativa is highly adaptable and can be grown in arid and semi-arid areas in the Western and Southwestern United States [18] and on marginal, low-fertility, and saline soils [19]. C. sativa is cold-tolerant and capable of surviving late-spring freezes [10] making it suitable as an oilseed crop in Northern Nevada where such freezes can occur.…”
Section: Introductionmentioning
confidence: 99%
“…By using ET o or ET r with the FAO-56 dual K c approach, soil water evaporation and plant transpiration can be independently estimated on a daily basis, and a simple daily soil water balance computation enables calculations of water stress effects on ET in water-limited conditions. In central Arizona, research at the Maricopa Agricultural Center (MAC) has developed FAO-56 approaches for irrigation management in alfalfa (Medicago sativa (L.) Lew; Hunsaker et al, 2002), camelina (Camelina sativa (L.) Crantz; Hunsaker et al, 2013), upland cotton (Gossypium hirsutum L.; Hunsaker et al, 2005aHunsaker et al, , 2015, guayule (Parthenium argentatum (A.) Gray; Hunsaker and Elshikha, 2017), and wheat (Triticum aestivium L.; Hunsaker et al, 2005bHunsaker et al, , 2007aHunsaker et al, , 2007b.…”
mentioning
confidence: 99%